William Golding’s Rites of Passage. A Case of Transtextuality - Nadal Blasco, Marita (Miscelánea: A Journal of English and American Studies, 1994)
More or less consciously, all authors rewrite the work of their predecessors, since it is impossible to escape the influence of previous writings. Golding’s Rites of Passage uses and abuses the conventions of earlier works very overtly, flaunting its condition of postmodern literary artifact. This paper shows how Rites of Passage makes use of all the five types of transtextual relationships that Genette defines in Palimpsestes —intertextuality, paratextuality, metatextuality, hypertextuality and archtextuality— through which this novel foregrounds its postmodernist flavour. Thus, while noting the complex transtextuality of Rites of Passage, we also point out its historiographic/metafictional character, since both features are closely related.